Six-minute walk test performance among school children aged 7-12 years living above 2300 meters in Jumla, Nepal - Thani, Kamal Prasad; Shrestha, Sandeep; Gautam, Uttara; Keshari, Munna; Sharma, Subash; Ashine, Amare Hailu (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: The Six-Minute Walk Test (6MWT) is a practical and widely used measure of submaximal functional exercise capacity. There are limited studies conducted in high altitude regions, particularly among children from hilly areas. Methods: A cross-sectional study was conducted among healthy school children in Jumla at altitudes ranging from 2,300 to 2,900 meters. Anthropometric data (height, weight, BMI) were recorded. The 6MWT was performed according to the American Thoracic Society (ATS) guidelines. Pre- and post-test heart rate, oxygen saturation (SpO2), and perceived exertion (modified Borg scale) were measured. Results: A total of 120 children (60 boys, 60 girls) were included. The mean 6MWD was 585 ± 42 meters. Boys walked slightly farther than girls, but this difference was not statistically significant (p = 0.068). Height and age showed a strong positive correlation with 6MWD (both p < 0.001). Baseline SpO2 was lower than sea-level norms (mean 94.2%), demonstrating highaltitude acclimatization, with a slight, non-pathological desaturation post-exercise. Conclusion: This study provides preliminary reference values for the 6MWT in children residing at high-altitude in Jumla, Nepal. Anthropometric factors, particularly height and age, are primary determinants of walking distance in this population.